Transcriptome expression profile of compound-K-enriched red ginseng extract (DDK-401) in Korean volunteers and its apoptotic properties - Ahn, Jong Chan; Mathiyalagan, Ramya; Nahar, Jinnatun; Ramadhania, Zelika Mega; Kong, Byoung Man; Lee, Dong-Wook; Choi, Sung Keun; Lee, Chang Soon; Boopathi, Vinothini; Yang, Dong Uk; Kim, Bo Yeon; Park, Hyon; et al. (Frontiers in Pharmacology, 2022)
Ginseng and ginsenosides have been reported to have various pharmacological effects, but their efficacy depends on the intestinal absorption. Compound K (CK) is also gaining prominence for its biological and pharmaceutical properties. In this study, CK-enriched fermented red ginseng extract (DDK-401) was prepared by enzymatic reactions. To examine its pharmacokinetics, a randomized, single dose, 2 sequence, crossover study was performed in eleven healthy Korean male and female volunteers. The volunteers were assigned to take a single oral dose of one of two extracts, DDK-401 or common red ginseng extract (DDK-204), in the first period. After a 7-day washout, they received the other treatment. The pharmacokinetics of DDK-401 showed that the maximum plasma concentration (Cmax) occurred at 2.4 hr, Tmax was 184.8±39.64 ng/mL, and AUC0–12hr was 11.3±4.66 ng·hr/mL, which were all better than DDK-204. The maximum CK absorption in the female volunteers was higher than that in the male volunteers. The differentially expressed genes from the male and female groups were subjected to a KEGG pathway analysis, which returned results in the cell death pathway, such as apoptosis and necroptosis. In cytotoxicity tests, DDK-401 and DDK-204 were not particularly toxic in HaCaT cells, but at a concentration of 250 µg/mL, DDK-401 had much higher toxicity in human lung cancer (A549) cells than DDK-204. DDK-401 showed a stronger antioxidant capacity than DDK-204 in both the DPPH and potassium ferricyanide-reducing power assays. DDK-401 reduced ROS production in normal cells (HaCaT) with induced oxidative stress and led to apoptosis in lung cancer cells (A549). In the RNA sequence analysis, a signaling pathway with selected marker genes was assessed by RT-PCR. In the HaCaT cells, DDK-401 and DDK-204 did not regulate FOXO3, TLR4, MMP-9, or p38 expression, whereas in the lung cancer A549 cells, DDK-401 downregulated of the expression of MMP9 and TLR4 and upregulated the expression of p38 and caspase 8 genes, compared with DDK-201. The results suggest that DDK-401 could act as a molecular switch for those two cellular processes in response to cell damage signaling and that it could be a potential candidate for further evaluation in health promotion studies.